The Influence of Gross Regional Domestic Product, Number of Population, and Number of Nusantara Tourists on Regional Original Income - Haiqal Imansyah; Bambang Sambodo; Alamsyahbana, Muhammad Isa; Rezario Febrianta Chandra; Masyitah As Sahara (Future Science, 2024)
The aim of this research is to find out whether the original income of districts/cities in Aceh Province is influenced by GRDP, population and number of domestic tourists. The total sample is 23 regencies/cities in Aceh Province. Quantitative methods are used as research methods, with the data used being secondary data obtained through publications and the official website of the Indonesian Central Statistics Agency, the Directorate General of Financial Balance (DJPK), and the Information and Documentation Management Officer (PPID). The research results partially prove that regional original income is not influenced by GRDP, population and number of domestic tourists. This was proven in the partial test, the significance value resulting from all independent variables was less than 0.05. However, regional original income is jointly (simultaneously) influenced by GRDP, population and number of domestic tourists, as can be seen in the simultaneous test with an f-count value of 13.91490 which is greater than the f-table of 2.745915. Based on the research results, the conclusion that can be drawn is that local revenue in the District/City of Aceh Province is not partially influenced by GRDP, population and number of domestic tourists. But simultaneously PAD can be influenced by GRDP, population and number of domestic tourists. So that districts/cities in Aceh Province are considered to be less able to utilize regional resources that can increase their original regional income, both in the economic, demographic and tourism sectors.